2019
DOI: 10.17576/jsm-2019-4805-04
|View full text |Cite
|
Sign up to set email alerts
|

Yield Enhancement of Recombinant α-Amylases in Bacillus amyloliquefaciens by ARTP Mutagenesis-Screening and Medium Optimization

Abstract: α-Amylase is the most extensively applied enzyme in industry. There is an urgent need for improvement on the yield of α-amylases currently. Herein, a strategy which combined Atmospheric and Room Temperature Plasma (ARTP) mutagenesis tool for construction of mutant library of Bacillus amyloliquefaciens with a 24-well plates screening technique was adopted to improve the yield of recombinant Bacillus amyloliquefaciens α-amylases (BAA). A mutant strain named B. amyloliquefaciens ZN mut-7# was obtained, and the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Similar results were reported by Swain et al (2006) in which the optimum activity of α-amylase extracted from B. subtilis CM3 was found at pH 5.0-9.0 and 50-70 C. While Awasthi et al (2018a,b) reported four isolates of Bacillus with maximum amylase activity at pH 5.3-8.2 and 60 C. The level of amylase production was found to depend on the temperature effects on the growth of the organism. The temperature range of 35-80 C has earlier been reported to favour the growth α-amylase -producing bacteria (Bajpai and Bajpai, 1989;Burhan et al, 2003;Ibrahim et al, 2013;Asad et al, 2014;Xu et al, 2019). However, temperatures above 65 C were found to negatively affect the activity of enzymes while a further increase in temperature caused a decline in the activity of α-amylase (Figure 5) possibly due to enzyme denaturation which led to inhabitation (Anto et al, 2006).…”
Section: Screening Of α-Amylase Productionmentioning
confidence: 89%
“…Similar results were reported by Swain et al (2006) in which the optimum activity of α-amylase extracted from B. subtilis CM3 was found at pH 5.0-9.0 and 50-70 C. While Awasthi et al (2018a,b) reported four isolates of Bacillus with maximum amylase activity at pH 5.3-8.2 and 60 C. The level of amylase production was found to depend on the temperature effects on the growth of the organism. The temperature range of 35-80 C has earlier been reported to favour the growth α-amylase -producing bacteria (Bajpai and Bajpai, 1989;Burhan et al, 2003;Ibrahim et al, 2013;Asad et al, 2014;Xu et al, 2019). However, temperatures above 65 C were found to negatively affect the activity of enzymes while a further increase in temperature caused a decline in the activity of α-amylase (Figure 5) possibly due to enzyme denaturation which led to inhabitation (Anto et al, 2006).…”
Section: Screening Of α-Amylase Productionmentioning
confidence: 89%
“…The reasons for lower/varied specific activity could be enzyme production and assay conditions, such as pH and temperature, were not optimized in this study. Amylase-producing enzymes have optimum growth and enzyme-producing conditions (pH and temperature) [24,25,30].…”
Section: Discussionmentioning
confidence: 99%
“…The alkaline phosphatase activity of the mutant strain S-52 was determined to be 12,110.6 U/L, which is 4.67 times greater than that of the original strain. ARTP has also been employed in the production of other enzymes, such as protease [ 34 , 35 ], alginate lyase [ 36 ], α-amylase [ 37 ], and alkaline protease [ 38 ]. The mutant strains exhibited significantly higher enzyme production capacity compared to the original strain, demonstrating the effectiveness of ARTP in improving enzyme yield.…”
Section: Application Of Artp To Bacteriamentioning
confidence: 99%